ORGANIZATION OF LEVEL BASED TEACHING OF FOREIGN LANGUAGES AT THE NON-LINGUISTIC UNIVERSITIES - Khazhgaliyeva, G. Kh. (ЗКАТУ им. Жангир хана, 2022)
This article deals with the priorities of level based teaching of foreign languages at the nonlinguistic universities and contains recommendations for level based learning. Attention is paid to the most urgent problems that require further development. A level approach to foreign language teaching is considered as both a practical strategy in organizing foreign language teaching at the university and a factor that contributes to the development of educational system. Level based language learning as an important element of general and professional culture and the medium of professional communication has gained special relevance. For students of nonlinguistic universities, the study of a professionally oriented language is not only a means of mastering the future specialty, but also the ability to develop competent professional communication in the future and allow them to be easily adapted to the dynamically changing labor conditions. In addition, the emergence of changes in the education system also contributed to the acceleration of the development of society in the conditions of multinational Kazakhstan.
Khazhgaliyeva, G. Kh. ORGANIZATION OF LEVEL BASED TEACHING OF FOREIGN LANGUAGES AT THE NON-LINGUISTIC UNIVERSITIES / G. Kh. Khazhgaliyeva, Г. Х. Хажгалиева. - Текст : непосредственный // Ғылым және білім: Қазіргі көзқарас жағдайындағы ғылым мен білімді дамытудың өзекті мәселелері: ХХІІ халықаралық ғылыми-практ. конф. материалдары (12 сәуір 2022 ж.) = Наука и образование: Актуальные вопросы развития науки и образования в условиях современных вызовов: мат. ХХІІ междунар. науч.-практ. конф. (12 апреля 2022 г.) = Science and education: topical issues of the development of sciense and education in the context of modern challenges: mat. of the XXII International Scientific and Practical Conf. (12 aptil 2022). - Уральск: ЗКАТУ им. Жангир хана. - 2022. - № 2 (67) : прил. № 2. - Р. 296-306 (Uralsk).
Keywords: level based teaching; international educational standards; learning of foreign languages; level approach; lexical and grammar skills; научный журнал; зкату